Children's resource distribution in a third-party moral transgression - Tan, Wendi Hui Min (Nanyang Technological University, 2021)
Few studies have looked at resource distribution to recipients of different moral valence. Resource distribution studies mostly use identical items, but items can differ in types and desirability, which can in turn influence distribution patterns. [1st Award]